On the types of franchise fees - Miljković Strahinja D. (Zbornik Radova Pravnog Fakulteta u Nišu, 2016)
By accessing a franchising network at the moment of contracting a franchising agreement, a franchisor concedes the franchise package of rights to a franchisee. Making use of the benefits provided by business operations in a developed and market-recognizable franchise network, the franchisee has certain contractual obligations which are embodied in financial compensation to the franchisor. The franchisee is obliged to pay the franchisor certain fees, such as: 1) the initial franchise fee; 2) the continuing franchise fee and 3) the advertising fee. The initial franchise fee may be regarded as 'an entry fee', i.e. a ticket to a franchising network. The continual fee is an active revenue which allows a franchisor to finance the activities of rendering a wide range of services to a franchisee and, concurrently, to make profit. The advertising fee is paid to a franchisor by a franchisee for services rendered in the field of advertising business. In the author's opinion, the professional public in the country should pay considerable attention to this topic, with specific reference to the experiences of countries with developed franchising business practices.